Implantation of intrastromal corneal segments for the correction of posttraumatic cicatricial corneal astigmatism - V. V. Neroev; E. V. Chentsova; D. S. Belyaev; A. V. Penkina (Российский офтальмологический журнал, 2018)
Purpose: to study the possibility of the correction of post-traumatic cicatricial corneal astigmatism (PССA) by implanting intrastromal corneal segments (ICS) with a femtosecond laser. Materials and methods. We operated 28 patients (28 eyes) aged 18 to 70 (averagely 37.5 ± 13.2 years) with astigmatism from 2.5 to 10.0 D. Prior to ICS implantation, astigmatism as measured by autokeratorefractometry was 5.7 ± 2.8 D, by keratotopography 6.0 ± 2.6 D, and by visometry - 6.1 ± 2.1 D. In all cases the spherical equivalent of refraction (SER) was negative, averaging 4.5 ± 2.1 D. Results. The major refractive changes in the cornea were manifested in the first month after ICS implantation. The cylindrical component of clinical refraction and SER decreased significantly 6 months after the operation. Post-surgical uncorrected visual acuity proved to average 0.29 ± 0.09, which was significantly (by 0.19 ± 0.08) higher than before surgery (0.10 ± 0.06). Conclusion. The effectiveness and safety of PCCA correction by ICS implantation of ICS could be confirmed. The procedure was found to have a hyperopic effect. The intrastromal corneal tunnel formed for ICS was found to be precise, as shown by optical coherence tomography. It must however be borne in mind that residual astigmatism and residual SER require additional correction in all patients who underwent ICS implantation // Russian Ophthalmological Journal, 2017; 1: 36-42. doi: 10.21516/2072-0076-2017-10-1-36-42.